PENERAPAN BUSINESS CONTINUITY MANAGEMENT PADA MASA PANDEMI COVID-19 DI PT BRANTAS ABIPRAYA - Tatan Sukwika; Wahyu Hery Sasongko (Distribusi - Journal of Management and Business, 2021)
Abripraya has implemented Business Continuity Management (BCM) as an effort to keep business processes running well under any risk conditions, including when the Covid-19 virus pandemic occurs. However, in Abipraya, there are still business risks that need to be resolved, namely violations of SOPs related to preventing Covid-19. This study aims to determine which risk groups are at high risk for applying Business Continuity Management in Abipraya during the Covid-19 pandemic. Data collection methods are used through field observations, documentation of activities, and interviews related to the object in the study. The results found six risks with a very high level, one chance with a high level, and a medium level due to violations of BCM implementation by Abipraya's external parties. The majority of breaches of the implementation of BCM by period-specific project workers such as vendors and subcontractors, visiting visitors, and online motorcycle taxi drivers. In conclusion, about 75% of the risk group with a very high-risk category for the BCM Abipraya during the Covid-19 pandemic. The managerial implication is to disseminate regulations, especially to external parties, and implement periodic mitigation plans to reduce high risk.